Synthetic bone substitute engineered with amniotic epithelial cells enhances bone regeneration after maxillary sinus augmentation. - Barbara Barboni (Public Library of Science (PLoS), 2013)
Background Evidence has been provided that a cell-based therapy combined with the use of bioactive materials may significantly improve bone regeneration prior to dental implant, although the identification of an ideal source of progenitor/stem cells remains to be determined. Aim In the present research, the bone regenerative property of an emerging source of progenitor cells, the amniotic epithelial cells (AEC), loaded on a calcium-phosphate synthetic bone substitute, made by direct rapid prototyping (rPT) technique, was evaluated in an animal study. Material and methods Two blocks of synthetic bone substitute (∼0.14 cm(3)), alone or engineered with 1×10(6) ovine AEC (oAEC), were grafted bilaterally into maxillary sinuses of six adult sheep, an animal model chosen for its high translational value in dentistry. The sheep were then randomly divided into two groups and sacrificed at 45 and 90 days post implantation (p.i.). Tissue regeneration was evaluated in the sinus explants by micro-computer tomography (micro-CT), morphological, morphometric and biochemical analyses. Results and conclusions The obtained data suggest that scaffold integration and bone deposition are positively influenced by allotransplantated oAEC. Sinus explants derived from sheep grafted with oAEC engineered scaffolds displayed a reduced fibrotic reaction, a limited inflammatory response and an accelerated process of angiogenesis. In addition, the presence of oAEC significantly stimulated osteogenesis either by enhancing bone deposition or making more extent the foci of bone nucleation. Besides the modulatory role played by oAEC in the crucial events successfully guiding tissue regeneration (angiogenesis, vascular endothelial growth factor expression and inflammation), data provided herein show that oAEC were also able to directly participate in the process of bone deposition, as suggested by the presence of oAEC entrapped within the newly deposited osteoid matrix and by their ability to switch-on the expression of a specific bone-related protein (osteocalcin, OCN) when transplanted into host tissues.